HUBUNGAN ANTARA FREKUENSI PAPARAN PORNOGRAFI DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA SMA/SEDERAJAT DI WILAYAH KERJA PUSKESMAS SUKAWATI I KABUPATEN GIANYAR BALI 2014 - Muhammad Aidil (DiscoverSys Inc., 2015)
One of the social problem that make big problem nowadays is premarital sexual behavior amongst teenagers.This problem can lead to many impacts such as the high incidence of HIV/AIDS and Sexual TransmitedDisease. According to some research, premarital sexual behavior is influenced by pornography exposuretowards teenagers. The aim of this study is to detect the relationship between frequency of pornographyexposure towards the premarital sexual behavior in high school teenagers Sukawati Public Health Centre IIÂ working place. The design for this research is quantitative study with analytic crossâ€sectional design. To collect the sample we use questioner without the name of the respondent amongst 136 students in two high school. For analysis we use Chi Square analysis using computer software. In this study, 19,1% respondent has done a premarital sexual behavior. At bivariate analysis, frequency of pornographic exposure (p=0,615) donâ€™t have a significance relationship with premarital sexual behavior. For this study, the significance is p value below 0,05. Frequency of pornographic exposure donâ€™t have a significant relationship with premarital sexualÂ behavior.Â